RANGKUMAN dan pengayaan bahasa Inggris kelas VI SD semester 2 / Hubertus Hari Listyanto...[et al] ; editor, Maria Agustina S ; ilustrator, Hernawan - Hubertus Hari Listyanto; Maria Agustina S; Hernawan (Kanisius, 2016)
88 hlm. : ilus. ; 25 cm.